2022
DOI: 10.1039/d1mh01918j
|View full text |Cite
|
Sign up to set email alerts
|

Polymer dielectric films exhibiting superior high-temperature capacitive performance by utilizing an inorganic insulation interlayer

Abstract: Utilizing an MgO insulation interlayer reduces electrical conduction and enhances the electric breakdown strength of PEI dielectric films, this facile but effective method significantly improves the high temperature capacitive performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…22 Efforts have been devoted to reducing the leakage current of polymer dielectrics at elevated temperatures to improve the electrostatic energy storage performance. 12,[23][24][25][26][27] One effective approach to reducing the leakage current is to impede the charge injection from the electrode into the dielectric materials, which has been realized by adding a high insulative layer between the polymer surface and metal electrodes. 5,9,21,[27][28][29] For instance, growing the SiO 2 layer on the surface of PEI film can create an effective electron barrier at the interface between the electrode and the dielectric, which blocks the charge injection and thus reduces the leakage conductance.…”
Section: Introductionmentioning
confidence: 99%
“…22 Efforts have been devoted to reducing the leakage current of polymer dielectrics at elevated temperatures to improve the electrostatic energy storage performance. 12,[23][24][25][26][27] One effective approach to reducing the leakage current is to impede the charge injection from the electrode into the dielectric materials, which has been realized by adding a high insulative layer between the polymer surface and metal electrodes. 5,9,21,[27][28][29] For instance, growing the SiO 2 layer on the surface of PEI film can create an effective electron barrier at the interface between the electrode and the dielectric, which blocks the charge injection and thus reduces the leakage conductance.…”
Section: Introductionmentioning
confidence: 99%
“…1 These materials are suitable for the fabrication of nano-crystals, nano-rods, nanowires, and nanoparticles, and are able to be altered to suit various constructions. [1][2][3][4][5] As a result, technology based on perovskites is estimated to be more cost-effective and appropriate than silicon-based technology. 6 The scientic community has especially interested in halide hybrid perovskites from 2009 to 2020.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the scholars have analyzed and compared the coal chemical industry with other industries. Through the comparison between the new coal chemical technologies with the traditional ones has concluded that the former is more competitive in terms of energy consumption, resource utilization of "three wastes," as well as "zero" emissions and CCS namely carbon capture and storage [9][10][11]. The comparison between the coal chemical industry and other industries shows that the former is more competitive in water resource utilization, pollutant emission and treatment, and carbon dioxide capture; and in terms of economic benefits, CTL and coal-toolefins would become more competitive than petroleum products when Brent oil prices exceed US$80/barrel and US$50/barrel, respectively [12,13].…”
Section: Literature Reviewmentioning
confidence: 99%